A new robust tolerance design method for electromechanical device based on variable contribution rate coefficients. (2nd September 2017) - Deng, Jie; Ye, Xuerong; Lin, Yigang; Li, Qiuyang; Zhai, Guofu
ABSTRACT: The consistency of batch electromechanical device is influenced seriously by the uncertainty in manufacturing process. Robust tolerance design (RTD) can reduce the impact of uncertainty on the batch products consistency. However, in the traditional RTD method, the contribution rate coefficients of design parameters remain constant during the tolerance optimisation process, which badly affects the accuracy of optimisation. In the paper, a new RTD method of automatic optimisation is proposed based on the variation of contribution rate coefficients. During the tolerance optimisation process, the contribution rate coefficients will be recalculated for each iteration, the step size of tolerance decrease for each parameter can be automatically adjusted according to the difference between the current consistency index and the optimisation target. Compared with the traditional Taguchi RTD method, the optimisation accuracy can be obviously improved by the new method proposed in the paper.